2020
DOI: 10.3386/w27976
|View full text |Cite
|
Sign up to set email alerts
|

The (Missing) Relation Between Announcement Returns and Value Creation

Abstract: Ben-David is a cofounder and a partner in an investment advisor that manages investment accounts. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Other researchers have also found that similarity between acquirer and target, enabling positive transfer of knowledge, results in positive acquisition performance measured through announcement time CAR (Finkelstein and Haleblian 2002;Hayward 2002). However, Ben-David et al (2020) showed that, contrary to the widely-held view of announcement returns being reflective of long-term acquisition outcomes, they are uncorrelated, casting doubt on the usefulness of announcement returns.…”
Section: Market Measuresmentioning
confidence: 96%
“…Other researchers have also found that similarity between acquirer and target, enabling positive transfer of knowledge, results in positive acquisition performance measured through announcement time CAR (Finkelstein and Haleblian 2002;Hayward 2002). However, Ben-David et al (2020) showed that, contrary to the widely-held view of announcement returns being reflective of long-term acquisition outcomes, they are uncorrelated, casting doubt on the usefulness of announcement returns.…”
Section: Market Measuresmentioning
confidence: 96%